Teori Projecting Back dan Argumentum E-Silentio Joseph Schact Serta Aplikasinya dalam Studi Kritik Hadis - Zidna Zuhdana; Nurus; Tsuroya, FatiaInast; Mustofa, Ahmad Zainal (Al-Bukhari : Jurnal Ilmu Hadis, 2020)
This article describes the viewpoint of Joseph Schacht, who argues that hadiths had been used as a secondsources of Islamic law since the caliphates periods. Schacht was an orientalist who studied the hadith usingacademic reasoning. He criticized the authentification of hadiths using Projecting Back theory and theArgumentum E-Silentio. Thus, Schacht denied the truth of the Prophet's traditions the way Muslims do believe in. According to him, hadiths were merely speeches and atitudes of scholars of the second and third centuries of Hijriah who attach their own words to the Prophet to gain Muslims supports for their personal interests. By using a research library and analytical descriptive methods, this article alsopresentthe application example of the two theories in the chosen hadith.